2013
DOI: 10.1093/rpd/nct043
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of absorbed dose to thyroid in patients treated with radiotherapy for various cancers

Abstract: This study is aimed at the evaluation of the absorbed dose to the thyroid gland from scattered/primary radiations in patients who have undergone radiotherapy. In this study, the skin entrance dose (SED) on the anterior neck at the level of the thyroid gland was measured using thermoluminescent dosimeters for 57 patients during radiotherapy with (60)Co teletherapy unit. Phantom dosimetry was also performed to find the correlation between the SED and the dose at the depth of the thyroid. SED of patients treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Besides, we also analyzed the correlative relationship between the measured ESD and the simulated AD. The thyroid ESD was higher than the mean value of AD, which was consistent with the results in reference (11). The attenuation of machine leakage and low-energy scattering radiation might account for it.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, we also analyzed the correlative relationship between the measured ESD and the simulated AD. The thyroid ESD was higher than the mean value of AD, which was consistent with the results in reference (11). The attenuation of machine leakage and low-energy scattering radiation might account for it.…”
Section: Discussionsupporting
confidence: 91%
“…However, the reported measurement procedures were usually inefficient, where 85 points could be involved for measurement. 11 The thyroid dosimetry could also be evaluated with AD simulated in treatment planning system (TPS). 2,12,13 Nevertheless, uncertainties related to beam modeling and intrafraction management might lead to inaccuracies in dose delivery, making the dose assessment inaccurate.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of exposed cases, particularly exposed cases with doses of 30 Gy or more, was basically too small to fit more complex models. It is difficult to compare given doses to absorbed doses; however, as an example, for Hodgkin Lymphoma patients Gul et al [ 7 ] estimate that 64-94 % of the given dose is also absorbed by the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Besides leukaemia and breast cancer, thyroid cancer is most frequently associated with radiation exposure [ 2 ]. Gul et al [ 7 ] identified high doses absorbed by the thyroid gland due to scattered radiation during radiotherapy for breast cancer, lung cancer, Hodgkin’s lymphoma and tumours in the head and neck region using CO 60 teletherapy. An association between the occurrence of thyroid adenomas and the radiation dose received during childhood cancer treatment has been recently shown [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[8] Several studies have shown that women with breast cancer have an additional risk for other cancers such as thyroid cancer. [121314] Many studies evaluated the risk of secondary cancer in radiotherapy of breast cancer patients and also a great variety can be seen in their methodology (measurement[15] or calculation[16]), dosimetry mediums (phantom[1718] or patient[19]), dosimeters (thermoluminescent dosimeter [TLD], metal-oxide-semiconductor field-effect transistor or other types),[131720] treatment techniques (standard or complex),[1718] type of treatment machines, reported quantity (medium dose, equivalent dose, and skin dose),[202122] and the risk models (International Radiation Protection Commission [ICRP] or biological effects of ionizing radiation [BEIR]). [1823]…”
Section: Introductionmentioning
confidence: 99%